Business Actors in Peace Mediation Processes. (June 2016) - Iff, Andrea; Alluri, Rina M.
Abstract: Even though the relevance of business actors in peace processes is increasingly acknowledged, analysis of their particular roles and contributions remain sparse in peace mediation literature. This is despite the fact that such knowledge would be highly relevant for supporting mediation processes such as those ongoing in Colombia or the Philippines. This article looks at the involvement of business actors in mediation processes by tracing analysis along the entry points for involvement, the different roles that business actors can play and the limitations they face. The empirical data shows that business actors mainly play a role during the pre‐ and mediation phase and therein often as a support‐giver to the mediation process. Furthermore, most of the involvement does not take place at track‐1 level but rather at track‐2 mediation processes, where mainly local business play an important role. In contrary to what is postulated by some of the literature, the relevance of utilitaristic motives is not problematic; rather a monetary motivation can also foster the credibility in a political process where a lot is at stake.